The Relationship between Colonization by Moraxella catarrhalis and Tonsillar Hypertrophy - Mirela C. M. Prates; Edwin Tamashiro; José L. Proenca-Modena; Miriã F. Criado; Tamara H. Saturno; Anibal S. Oliveira; Guilherme P. Buzatto; Bruna L. S. Jesus; Marcos G. Jacob; Lucas R. Carenzi; Ricardo C. Demarco; Eduardo T. Massuda; et al. (Canadian Journal of Infectious Diseases and Medical Microbiology)
We sought to investigate the prevalence of potentially pathogenic bacteria in secretions and tonsillar tissues of children with chronic adenotonsillitis hypertrophy compared to controls. Prospective case-control study comparing patients between 2 and 12 years old who underwent adenotonsillectomy due to chronic adenotonsillar hypertrophy to children without disease. We compared detection of Streptococcus pneumoniae, Haemophilus influenzae, Staphylococcus aureus, Pseudomonas aeruginosa, and Moraxella catarrhalis by real-time PCR in palatine tonsils, adenoids, and nasopharyngeal washes obtained from 37 children with and 14 without adenotonsillar hypertrophy. We found high frequency (>50%) of Haemophilus influenzae, Streptococcus pneumoniae, Moraxella catarrhalis, and Pseudomonas aeruginosa in both groups of patients. Although different sampling sites can be infected with more than one bacterium and some bacteria can be detected in different tissues in the same patient, adenoids, palatine tonsils, and nasopharyngeal washes were not uniformly infected by the same bacteria. Adenoids and palatine tonsils of patients with severe adenotonsillar hypertrophy had higher rates of bacterial coinfection. There was good correlation of detection of Moraxella catarrhalis in different sampling sites in patients with more severe tonsillar hypertrophy, suggesting that Moraxella catarrhalis may be associated with the development of more severe hypertrophy, that inflammatory conditions favor colonization by this agent. Streptococcus pneumoniae, Staphylococcus aureus, Haemophilus influenzae, and Moraxella catarrhalis are frequently detected in palatine tonsils, adenoids, and nasopharyngeal washes in children. Simultaneous detection of Moraxella catarrhalis in adenoids, palatine tonsils, and nasopharyngeal washes was correlated with more severe tonsillar hypertrophy.